Direct Anterior Approach for AO43B/43C Pilon Fracture Fixation Demonstrates No Difference in Rate of Reoperation Compared to Other Surgical Approaches - Laura Sokil MD; Liam H. Wong MD; Elizabeth Roti BS; Graham DeKeyser MD; Zachary Working MD; Darin Friess MD; James Meeker MD (Foot & Ankle Orthopaedics)
Category: Trauma; Ankle Introduction/Purpose: The direct anterior (DA) approach is commonly used for reconstructive procedures to treat posttraumatic ankle osteoarthritis (PTOA), however, literature investigating utilization of the DA approach (defined as the interval between the tibialis anterior tendon and extensor hallucis longus tendon) for initial fixation of pilon fractures is lacking. This retrospective study of patients undergoing fixation of pilon fractures hypothesizes that there is no difference in reoperation rate for patients whose pilon fractures were treated with DA approach. Methods: A retrospective radiographic and chart review of patients undergoing surgical fixation of tibial plafond fractures over a nine year period (2013-2022) at an urban, level 1 trauma center was undertaken. Review of operative notes for reoperation for infection, PTOA, nonunion and symptomatic hardware was utilized to determine reoperation rates. Injuries were radiographically stratified by AO/OTA classification, and quality of fracture reduction was assessed via measurement of the lateral distal tibial angle (LDTA) and lateral talar station (LTS) at the first postoperative radiograph. Likelihood of reoperation within one year of index surgery was analyzed using Kaplan-Meier estimations. Reoperation risk factors were determined with multivariable logistic regression analyses created using a backwards stepwise process. Results: 135 fractures in 130 patients met inclusion criteria; 44 fractures were treated via a DA approach, 91 treated via all other approaches, many in combination. Between groups, AO/OTA classification, demographics, injury characteristics and operative time were no different. Overall reoperation rate was 40.7%. There was no significant difference between DA and all other approaches in rate of reoperation for infection (2.3% vs. 10%, p=0.21), nonunion (15.9% vs. 16.5%, p=1), PTOA (9.1% vs. 7.8%, p=1) and removal of symptomatic hardware (25% vs. 36.3%, P=0.27). Multivariable regression showed DA approach was associated with lower risk of reoperation within one year (OR 0.25, 95% CI 0.07-0.71, P=0.02). The DA group lateral talar station (LTS) was significantly greater (more anterior) by 0.9mm (2.75mm DA vs. 1.85mm all others, P=0.01). Conclusion: Utilization of the direct anterior approach to the ankle for initial fixation of pilon fractures has no difference in overall reoperation rates and a lower likelihood of reoperation within one year compared to all other combinations of approaches to the tibial plafond. Radiographic outcomes were different between groups, but the clinical significance of this is unclear. The DA approach should be considered for fracture patterns amenable to its use and may offer benefit should reconstructive procedures become necessary.